Antiretroviral Side Effects on Adherence in People Living with HIV/AIDS - Arisudhana, Gede Arya Bagus; Sofro, Muchlis Achsan Udji; Sujianto, Untung (Nurse Media Journal of Nursing, 2018)
Background: Antiretroviral therapy is a lifelong treatment in people living with HIV/AIDS (PLWHA). Adherence is the key to the effectiveness of antiretroviral therapy. The administration of antiretroviral has some side effects that may affect patient adherence.Purpose: This study aimed to examine the impacts of antiretroviral side effects on adherence in PLWHA.Methods: This study used a correlational research design. The samples were 78 patients receiving antiretroviral therapy at the tropical disease and infection polyclinic in a hospital in Semarang. Purposive sampling was used to recruit the samples. Data on side effects of antiretroviral were obtained based on the patients’ reports, while data on adherence of pill consumption were obtained through the calculation of pills using pill count adherence rate. The collected data were analyzed using the Fisher’s exact test.Results: Results showed that the side effects of antiretroviral therapy influenced the antiretroviral adherence (p<0.001). Most of the side effects of antiretroviral reported by participants were nausea and dizziness. Some participants also reported weakness, difficult to concentrate, and diarrhea.Conclusion: The side effects of antiretroviral had negative impacts on patients’ antiretroviral therapy adherence. Therefore, nurses and health care providers of PLWHA should be able to recognize and give concern on antiretroviral side effect management.